Reconsidering the Minimum Voting Age in the United States. (March 2022) - Oosterhoff, Benjamin; Wray-Lake, Laura; Hart, Daniel
Several U.S. states have proposed bills to lower the minimum local and national voting age to 16 years. Legislators and the public often reference political philosophy, attitudes about the capabilities of teenagers, or past precedent as evidence to support or oppose changing the voting age. Dissenters to changing the voting age are primarily concerned with whether 16- and 17-year-olds have sufficient political maturity to vote, including adequate political knowledge, cognitive capacity, independence, interest, and life experience. We review past research that suggests 16- and 17-year-olds possess the political maturity to vote. Concerns about youths' ability to vote are generally not supported by developmental science, suggesting that negative stereotypes about teenagers may be a large barrier to changing the voting age.